Exchange rate pass-through in the euro area - Mariarosaria Comunale; Davor Kunovac (European Central Bank (ECB), 2017)
In this paper we analyse the exchange rate pass-through (ERPT) in the euro area as a whole and for four euro area members - Germany, France, Italy and Spain. For that purpose we use Bayesian VARs with identi?cation based on a combination of zero and sign restrictions. Our results emphasize that pass-through in the euro area is not constant over time - it may depend on a composition of economic shocks governing the exchange rate. Regarding the relative importance of individual shocks, it seems that pass-through is the strongest when the exchange rate movement is triggered by (relative) monetary policy shocks and the exchange rate shocks. Our shock-dependent measure of ERPT points to a large but volatile pass-through to import prices and overall very small pass-through to consumer in?ation in the euro area.
Keywords: E31; F3; F41; 330; Bayesian vector autoregression; consumer prices; exchange rate pass-through; import prices; inflation